PENGARUH MODEL COOPERATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI TEKANAN - Kartika Eka Kusuma Wardani; Tomo Djudin; Syukran Mursyid (Universitas Tanjungpura, Prodi Pendidikan Fisika, 2021)
The aim of this research was to determine the effectiveness of the implementation of the Cooperative Problem Solving model in enhancing the problem solving skills of students of SMPN 3 Sungai Raya in the pressure of solids. The research forms used was quasy experimental design with pretest-posttest control group design. The sample was students VIII G as an experimental class and VIII E was the control class which drawn by using intact group. The instrument used 5 essay questions. The result showed that there was no difference in the student problem solving skills of the control class and experimental classes before being given the implementation of Cooperative Problem Solving model and conventional learning (. There was difference in the student problem solving skills of the control class and experimental classes after being given the implementation of Cooperative Problem Solving model and conventional learning (. Implementation of Cooperative Problem Solving model effective to improve the student problem solving skills with effect size 1,89 (high category).